Kingship and memory in ancient Judah - Wilson, Ian Douglas 1981- (New York, NY Oxford University Press, 2017)
'Kingship and Memory in Ancient Judah' investigates kingship in Judean discourse, particularly in the early Second Temple era. In doing so, it contributes to our knowledge of literature and literary culture in ancient Judah and also makes a significant contribution to questions of history and historiographical method in biblical studies
Includes bibliographical references and index
Previously issued in print: 2017
Zielgruppe - Audience: Specialized
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Jews -- Kings and rulers; Jews -- History -- To 586 B.C; Memory -- Biblical teaching; Kings and rulers -- Biblical teaching; Bible ; Samuel ; Criticism, interpretation, etc; Bible ; Kings ; Criticism, interpretation, etc; Kings and rulers ; Biblical teaching; Jews ; Kings and rulers; Jews ; History ; To 586 B.C; Memory ; Biblical teaching; Bible; Jews; Kings and rulers; Memory; Hochschulschrift